Perceived Work-Family Balance Challenges Among Women Employees in the Department of Agrarian Reform Provincial Office - Narboneta, Mary Jean (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the perceived work–family balance challenges among women employees in the Department of Agrarian Reform Provincial Office in Masbate. Anchored on Work–Family Conflict Theory, Role Theory, and Work–Family Border Theory, the study explored how competing work and family demands affect women employees in a government workplace setting. A descriptive-quantitative research design was utilized, employing a researcher-made questionnaire validated by experts and tested for reliability through pilot testing and Cronbach’s alpha. The respondents were women employees of the Department of Agrarian Reform in Masbate selected through convenience sampling. Data were analyzed using frequency count, percentage, weighted mean, and Pearson correlation. Findings revealed that most respondents were young married professionals with moderate workloads and regular work schedules. The respondents generally experienced moderate work–family balance challenges, particularly in workload and time management, as well as emotional and physical stress. Women employees reported that work deadlines, time constraints, and overtime work interfered with family responsibilities and contributed to emotional strain and feelings of guilt. However, respondents generally perceived support from family and workplace and did not consider organizational policies and workplace support as major barriers to maintaining work–family harmony. The study also found that demographic characteristics had only a weak and statistically insignificant relationship with perceived work–family balance challenges. Respondents strongly supported measures such as wellness and stress management programs, counseling services, flexible work arrangements, strengthened parental benefits, and gender-sensitive supervisory practices to improve work–family balance. The study concludes that supportive organizational policies and employee wellness initiatives are essential in enhancing the emotional well-being and work–family balance of women employees in government institutions. The findings support Sustainable Development Goal (SDG) 5 on Gender Equality, SDG 8 on Decent Work and Economic Growth, and SDG 3 on Good Health and Well-Being by promoting gender-responsive workplace practices and employee welfare. The study contributes to institutional and social sustainability by encouraging policies that improve employee well-being, organizational effectiveness, and public service delivery within government agencies.